Developing OCEAN as a Game Based on English Learning in Teaching Vocabulary - Prastiwi, Afita Dewi; Saktiono, Maxima Ari (Department of English Language Education, UIN Sunan Ampel Surabaya, 2023)
Abstract This study applied Research and Development (R&D) study which developed game application based English learning. The purpose of this study is to improve the leaner’s vocabulary and reduce their anxiety in mastering English. Vocational maritime students had problem in memorizing vocabularies and based on the result of need analysis, they need a media that can ease them in learning English. This study followed some steps in developing the game application, those were; assessing need analysis, writing performance objective, instructional strategy’s development, instructional materials’ development and selection, implementation of formative and summative evaluation. The instrument of this study were questionnaire and interview to gain students response in need analysis process and in evaluation. OCEAN can catch the learner’s attention and decrease their anxiety in learning English. Most of students agree if the game improves their motivation and they can enjoy playing the game. The development of this game as an educational game has good impact and responses even though some improvements are needed.